The Translation of Silence : The Interdisciplinary Nature of A Book of Silence and its Implications for Translation - Pinho, Jorge Manuel Costa Almeida e (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
.